Interactions : (John Wiley & Sons, 2003)
Part of a series of CD-ROMs focusing on the examination of physiological processes within each system of the body, using animations, interactivity, and clinical correlations to enhance student understanding. At the heart of Interactions is a focus on core principles - homeostasis; communication; energy flow; fluid flow; and boundaries - that underscore the key relationships between structure and function as well as interrelationships between systems.